2014
DOI: 10.1136/bjophthalmol-2013-304465
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in glaucoma surgery in Scotland, England and Wales

Abstract: Trabeculectomy is the most commonly performed glaucoma operation. Aqueous shunts are rapidly increasing in the surgical management of glaucoma. During the study period, the ratio of trabeculectomy to aqueous shunts has reversed in the younger age group (0-14 years). Rates of cyclocyrotherapy to the ciliary body have dramatically declined while laser photocoagulation to the ciliary body is gaining wider acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
4
41
1
2
Order By: Relevance
“…A noticeable increase was also observed for aqueous shunts, although the total number remains very low compared with trabeculectomy or deep sclerectomy. These overall trends are very similar to those reported recently in Scotland, England and Wales,15 in Australia16 and in the USA 17…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A noticeable increase was also observed for aqueous shunts, although the total number remains very low compared with trabeculectomy or deep sclerectomy. These overall trends are very similar to those reported recently in Scotland, England and Wales,15 in Australia16 and in the USA 17…”
Section: Discussionsupporting
confidence: 90%
“…In fact, each country has its own particularities for delivering glaucoma surgical care and there is a high discrepancy in glaucoma surgical rates in different parts of the world 15. A recent survey reported an overall glaucoma surgery rate (GSR) ranging from 7 to 500, given per million inhabitants 13.…”
Section: Discussionmentioning
confidence: 99%
“…The TVT study found higher rates of success8 and fewer early postoperative complications with tube surgery compared with trabeculectomy in eyes with previous surgery 24. Our data do not allow separation of primary from secondary tube procedures, but the increase in glaucoma drainage device implantation may suggest that indications are expanding beyond refractory glaucoma 23. A survey of the American Glaucoma Society (AGS) in 2008 showed that AGS members are increasingly preferring glaucoma drainage devices in a range of clinical settings 25.…”
Section: Discussionmentioning
confidence: 76%
“…Similar changes have been observed in Europe and North America. Murphy et al 23 evaluated the rates of aqueous shunts in England, Scotland and Wales and found a sixfold increase between 2003 and 2012. In the USA, glaucoma drainage device insertions increased 53% over the same time period and in Canada rates increased 12-fold between 1992 and 2004 12.…”
Section: Discussionmentioning
confidence: 99%
“…5,14,15 One recent publication assessing trends in glaucoma surgery between 1993 and 2012 in Scotland, England, and Wales found a decline in the use of trabeculectomy and increases in the use of aqueous shunts to extraocular reservoir and ECP. 16 Desai et al 15 surveyed physician members of the American Glaucoma Society regarding their procedural preferences in particular clinical settings. With this method, they found that physician preference for aqueous shunt to extraocular reservoir increased significantly between 1996 and 2008, whereas the preference for conventional trabeculectomy use decreased significantly over the same time period.…”
Section: Discussionmentioning
confidence: 99%